Inhaled fluticasone furoate/vilanterol does not affect hypothalamic‐pituitary‐adrenal axis function in adolescent and adult asthma: randomised, double‐blind, placebo‐controlled study. (5th June 2013) - Allen, Ann; Schenkenberger, Isabelle; Trivedi, Roopa; Cole, Jeremy; Hicks, Wesley; Gul, Nadeem; Jacques, Loretta
Abstract Introduction Fluticasone furoate (FF) is a novel inhaled corticosteroid with 24‐h activity. FF is in development as a once‐daily treatment for asthma as monotherapy and in combination with vilanterol (VI), a long‐acting β2 agonist. Corticosteroids can have systemic effects on hypothalamic‐pituitary‐adrenal (HPA) axis function, potentially resulting in cortisol suppression. Objectives To assess the effect of FF/VI compared with placebo on the HPA axis by evaluating 24‐h weighted mean serum cortisol levels in adolescent and adult patients with persistent asthma. Methods One hundred eighty‐five patients with >12 weeks history of asthma were randomised in a 4:4:4:1 ratio to one of two once‐daily FF/VI treatments (100/25 μg or 200/25 μg), placebo or an active control group that received inhaled placebo plus one prednisolone 10 mg capsule daily for the last 7 days of the study. Twenty‐four‐hour serum and urinary cortisol was measured at baseline and on day 42. Results Non‐inferiority in 24‐h weighted mean serum cortisol after 6 weeks of treatment with once‐daily FF/VI at either strength was shown. Treatment ratios [95% confidence interval (CI)] to placebo for FF/VI 100/25 μg [0.99 (0.87–1.12)] or FF/VI 200/25 μg [0.97 (0.86–1.10)] indicated non‐inferiority of both FF/VI doses to placebo as the lower limit of the 95% CI was greater than the predefined 0.8. Prednisolone substantially reduced 24‐h weighted mean serum cortisol [treatment ratio to placebo 0.34 (0.28–0.41)]. FF/VI was well‐tolerated, and no safety concerns were identified. Conclusions FF/VI was found to be non‐inferior to placebo on HPA axis function, with no indication of significant cortisol suppression after 42 days.